Combination Of Betel Leaf Extract and Collagen as Liquid Anti-Inflammatory for Dental and Oral Tissue Treatment - Dewi, Ni Putu Dian Cipta (Interdental Jurnal Kedokteran Gigi (IJKG), 2025)
Introduction: Based on Riskesdas (Basic Health Research) data in 2018, the prevalence of oral and dental problems in Indonesia reached 57.6% with periodontal disease reaching 74.1%. Mouthwash can help reduce the number of bacteria that cause infections in the oral cavity. Natural ingredients that are often used are collagen membranes and betel leaves are commonly used as antiseptics. The purpose of this literature review is to discuss in detail the functions, applications, and challenges of using collagen membranes and betel leaves in dentistry, as well as to deepen the latest research related to incorporating these two materials. Review: Based on recent research, there is a combination of collagen membrane and betel leaf extract in dental treatment, especially to regenerate periodontal tissue. Collagen membrane coupled with betel leaf extract not only provides a scaffold to regenerate tissue but also as protection from bacteria, and microbes, as an anti-inflammatory, to accelerate the healing process, and as a prevention of infection. Collagen membrane and betel leaf have great potential in dentistry when combined, especially in tissue regeneration and infection prevention. Their combination may pave the way for the development of more effective and natural therapies in the treatment of dental and oral tissues. Conclusion: Collagen modification and betel leaf use in dental care offer great potential for improving oral health. Collagen supports tissue regeneration and wound healing, while betel leaf provides antimicrobial and anti-inflammatory benefits. The integration of these two ingredients in dental care products can improve the effectiveness of treatment and provide a more natural and effective solution to a variety of dental and gum problems. Kata kunci: Perawatan Gigi, Gigi dan Mulut, Kolagen, Daun Sirih, Modifikasi Kolagen